VARIASI STRUKTUR VOKALISASI OWA JAWA (Hylobates moloch Audebert, 1798) DI HUTAN LINDUNG PETUNGKRIYONO, PEKALONGAN, JAWA TENGAH - Maida, Sity; Sukandar, Paskal; Istiadi, Yossa (LPPM Universitas Negeri Jakarta, 2016)
Javan gibbon is one of an endemic species of Java with kind of unique vocalizations. Supported by a study which showed that every individual has the different anatomy vocal tract that will produce a different sound. Character vocalizations formed from the structure of vocalizations vary between individuals would be the identity of an individual so that there will be effective communication between the giver signal to the receiver. The objective of research is to find out the structure variation of Javan gibbon vocalizations.The research was accomplished in August-September 2015 at the Petungkriyono Protected Forest, Pekalongan, Central Java. The method used is the Focal Continuous sampling. Ratio coefficient of variation within and between female, indicates that the variable vocalizations vary between individuals, and the correct rate of individual identification yielded bydiscriminant function analysis using variable vocalizations was satisfactory (94,4%). Variable vocalization differentiatoris total great call duration (8,99-13,53 s), total great call duration excluding termination phase, duration pre-trill phase, duration introduction note (0,147-0,612 s), frequency range introduction note (408,54-1209,6 Hz), minimal frequency introduction note, maximal frequency introduction note, minimal frequency second trill note, minimal frequency at end of trill note, and minimal frequency range in trill. These vocalizations potentially allow individual recognition of animals.